Linear Discriminant Analysis dalam Memprediksi Financial Distress pada Bank Muamalat KCP Sukaramai Periode 2018-2022 - Syahdinar Nasution; Muhammad Irwan Padli Nasution; Tuti Anggraini (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the variables that can predict the financial distress of Islamic banks in Indonesia for the period to 2018-2022. Methodology: This research is quantitative with secondary data types. This study uses the variable (Return On Equity) ROE, (Cash To Deposits) CTD, (Loans To Assets) LTA as its independent variable, while the dependent variable is Financial Distress. The Financial Distress Indicator used in this study is the ROA categorized ratio (return on assets). Results: The results of this study indicate that 2 Independent financial ratio variables can predict financial distress, namely, ROE and CTD. These results are shown from the linear discriminant analysis using the independent variables and from the formation of the discriminant function coefficient values. Limitations: The Financial Distress Indicator used in this study is the ROA categorized ratio (return on assets). The analysis used in this study is a linear discriminant analysis that requires the dependent variable to be in the form of a category and is used to form the coefficient of the discriminant function. Contribution: Purposive sampling was conducted with a total sample of 14 Islamic Commercial Banks. This study is quantitative research with secondary data types.